THREATENING OF AIR ON THE MAGURSKI NATIONAL PARK IN THE AWARENESS OF THE LOCAL SOCIETY - KOWALSKA, Anna; SOBCZYK, Wiktoria (Trends in education, 2009)
In the article a history of creating Magurski National Park was described. A state of the ecological awareness of young people dwelling lands of the Park was presented. A very low level of the awareness of the young generation was stated.
Keywords: national park; threatening of air; the ecological awareness.